Tumor-specific activation of folate receptor beta enables reprogramming of immune cells in the tumor microenvironment - Zhang, Fenghua; Huang, Bo; Utturkar, Sagar M.; Luo, Weichuan; Cresswell, Gregory; Herr, Seth A.; Zheng, Suilan; Napoleon, John V.; Jiang, Rina; Zhang, Boning; Liu, Muyi; Lanman, Nadia; et al. (Frontiers in Immunology, 2024)
Folate receptors can perform folate transport, cell adhesion, and/or transcription factor functions. The beta isoform of the folate receptor (FRβ) has attracted considerable attention as a biomarker for immunosuppressive macrophages and myeloid-derived suppressor cells, however, its role in immunosuppression remains uncharacterized. We demonstrate here that FRβ cannot bind folate on healthy tissue macrophages, but does bind folate after macrophage incubation in anti-inflammatory cytokines or cancer cell-conditioned media. We further show that FRβ becomes functionally active following macrophage infiltration into solid tumors, and we exploit this tumor-induced activation to target a toll-like receptor 7 agonist specifically to immunosuppressive myeloid cells in solid tumors without altering myeloid cells in healthy tissues. We then use single-cell RNA-seq to characterize the changes in gene expression induced by the targeted repolarization of tumor-associated macrophages and finally show that their repolarization not only changes their own phenotype, but also induces a proinflammatory shift in all other immune cells of the same tumor mass, leading to potent suppression of tumor growth. Because this selective reprogramming of tumor myeloid cells is accompanied by no systemic toxicity, we propose that it should constitute a safe method to reprogram the tumor microenvironment.